2017
DOI: 10.3389/fped.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise, Pilot Study of Bovine Colostrum to Supplement the First Enteral Feeding in Preterm Infants (Precolos): Study Protocol and Initial Results

Abstract: Study protocolThe optimal feeding for preterm infants during the first weeks is still debated, especially when mother’s own milk is lacking or limited. Intact bovine colostrum (BC) contains high amounts of protein, growth factors, and immuno-regulatory components that may benefit protein intake and gut maturation. We designed a pilot study to investigate the feasibility and tolerability of BC as the first nutrition for preterm infants. The study was designed into three phases (A, B, and C) and recruited infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…In the gut, piglets fed with colostrum as minimal enteral nutrition (12), full enteral nutrition (16), or supplementation to donor milk (17,19) showed improved digestive functions, integrity, antiinflammatory responses, and NEC resistance. Several clinical trials are being performed in very preterm infants to document this for its clinical application (14,27,28). A pilot study has demonstrated the feasibility and tolerability of initial colostrum feeding (27,28), which has led to an ongoing randomized clinical trial powered for TFF as the primary outcome in very preterm infants (ClinicalTrials.gov Identifier: NCT03085277).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gut, piglets fed with colostrum as minimal enteral nutrition (12), full enteral nutrition (16), or supplementation to donor milk (17,19) showed improved digestive functions, integrity, antiinflammatory responses, and NEC resistance. Several clinical trials are being performed in very preterm infants to document this for its clinical application (14,27,28). A pilot study has demonstrated the feasibility and tolerability of initial colostrum feeding (27,28), which has led to an ongoing randomized clinical trial powered for TFF as the primary outcome in very preterm infants (ClinicalTrials.gov Identifier: NCT03085277).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials are being performed in very preterm infants to document this for its clinical application (14,27,28). A pilot study has demonstrated the feasibility and tolerability of initial colostrum feeding (27,28), which has led to an ongoing randomized clinical trial powered for TFF as the primary outcome in very preterm infants (ClinicalTrials.gov Identifier: NCT03085277). How colostrum feeding before or after suboptimal formula feeding protects or restores formula-induced intestinal impairment still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, nearly all studies described here investigated the effects of a single bioactive factor, while a synergistic action between several bioactive factors may be required to sort out its effects. One interesting strategy recently described is the use of bovine colostrum as a fortifier for mother’s milk or as a (partial) replacement for formula as it contains many active and potentially protective bioactive factors [ 67 , 68 , 69 ]. Four studies investigating the effects of bovine colostrum are currently ongoing ( Table S2 in Supplemental Materials).…”
Section: Discussionmentioning
confidence: 99%
“…The use of bovine colostrum is under investigation in preterm infants. In the safety phase of a pilot study bovine colostrum was well-tolerated in the pre-term infants, and further studies are ongoing ( 149 ).…”
Section: Bovine Immunoglobulins: Putative Mechanism Of Actionmentioning
confidence: 99%